Association of Prostate-Specific Antigen Density and Gleason score of Positive Surgical Margin with Biochemical Recurrence in Prostate Cancer - Fakhar, Vahid; Kamali, Koosha; Abolhasani, Maryam; Kaffash Nayeri, Reza; Emami, Maryam (Archives of Men's Health, 2022)
Background: We aimed to investigate the association between prostate specific antigen (PSA) density and Gleason score of the positive surgical (PSM) margin after radical prostatectomy with biochemical recurrence in patients with prostate cancer. Materials and Methods: In this retrospective cohort study, patients with prostate cancer referred to Hasheminejad Hospital in Tehran, Iran, during 2009-2019, who underwent radical prostatectomy were enrolled through the convenience sampling method. The follow-up period was determined as at least one year after radical prostatectomy to determine biochemical recurrence. Prostate-specific antigen density (PSAD) and the Gleason score of surgical specimen and positive surgical margins (PSM) were evaluated and their association with biochemical recurrences was investigated. Results: One hundred and three patients were assessed. The overall biochemical recurrence rate was 48.5% with a mean follow-up of 24 months (12-42 months) and an average time to biochemical recurrence of 18 months (16-20 months). BCR-free (Biochemical recurrence-free) survival rates of patients divided based on the PSAD cut-off point (0.205 ng/ml/cc) were significantly different using the log-rank test (P= 0.008) (85.7%, 57.1%, and 14.3% for values ≤ 0.205 ng/ml/c versus 55.8%, 20.9%, and 0% for values ˃ 0.205 ng/ml/cc, respectively for 1-, 2- and 3-year survival). Moreover, Cox regression showed that the Gleason score of PSM, the Gleason score of the surgical specimen, and the PSAD predicted biochemical recurrence more, respectively. Conclusion: PSAD and PSM Gleason scores were strong predictors of biochemical recurrence after radical prostatectomy and their use along with other common indicators including tumor grade and stage and PSA level can increase the accuracy of risk assessment in patients with prostate cancer.